The potential of AI-driven marketing in healthcare and related virtuous contemplations: A systematic review : English - Mapungwana, Pheyiye; Rathebe, P. C. (Orapuh Journal, 2025)
In the era of artificial intelligence (AI), marketing has transformed into a data-driven discipline that offers unprecedented opportunities for personalisation. However, this evolution raises significant ethical concerns regarding consumer trust and data privacy. This study explores the ethical implications of AI-driven marketing, particularly in the healthcare sector, emphasising the need for transparency and accountability. The primary aim of this research is to identify and discuss the ethical dilemmas that arise from integrating AI into marketing strategies. It seeks to highlight the balance between providing personalised services and maintaining consumer trust, while advocating responsible AI practices. A systematic literature review was conducted, focusing on articles published between 2015 and 2024. The search utilised the phrase “Ethical considerations in AI-driven marketing in healthcare”, enabling a comprehensive examination of the relevant literature. This approach facilitated an understanding of the historical context and current ethical challenges associated with AI in marketing. The findings indicate a significant increase in publications addressing AI ethics in marketing, particularly from 2018 to 2024. Key themes identified include the importance of transparency in data collection, the necessity of informed consent, and the ethical implications of personalisation versus intrusion. The analysis reveals that although AI can enhance customer engagement, it also poses risks related to data privacy and algorithmic bias. The study concludes that ethical considerations must be central to AI-driven marketing strategies. Organisations are urged to implement robust data protection measures, ensure transparency in AI usage, and respect consumer choices to foster trust. Striking a balance between personalisation and privacy intrusion is critical, as failure to address these ethical concerns could undermine consumer confidence and brand integrity.